Optimizing Invasive ECT sensor dimensions for conducting pipe: A simulation study - Ain Eazriena, Che Man; Yasmin, Abdul Wahab; Nurhafizah, Abu Talip Yusof; Suzanna, Ridzuan Aw; Mohd Mawardi, Saari; Ruzairi, Abdul Rahim; Yu, Sia Yee (Arqii Publication, 2025)
This simulation study aims to optimize the dimensions of an invasive Electrical Capacitance Tomography (ECT) sensor for conducting pipe applications. Conventional non-invasive ECT techniques are ineffective for conducting pipes, as they cannot penetrate the pipe wall. This study explores the use of an invasive ECT system to identify homogeneous and non-homogeneous dielectric media within conducting pipes. A simulation model is developed using the finite element method (FEM) and the Linear Back Projection (LBP) algorithm for image reconstruction, further enhanced by a global threshold method. Various sensor dimensions are tested in a 150 mm length steel pipe, with a sinusoidal waveform source of 25 Vpp and a frequency of 400 kHz applied to the model in both homogeneous and non-homogeneous dielectric media conditions. The simulation results reveal that the sensitivity and resolution of the invasive ECT system are significantly influenced by the sensor dimensions. Optimal sensor dimensions indicate that longer and wider sensors, covering approximately 80% of thesensor coverage area and 60% of the pipe length, provide higher electrical voltage and better resolution. Overall, this study provides valuable insights into optimizing invasive ECT sensor dimensions for observing dielectric media inside conducting pipes, significantly improving the accuracy and reliability of industrial process monitoring in both homogeneous and non-homogeneous media.